Control of Pan-tilt Mechanism Angle using Position Matrix Method - Hendri Maja Saputra; Arif Santoso; Midriem Mirdanies; Vikita Windarwati; Riastus Nayanti; Lukni Maulana (National Research and Innovation Agency, 2013)
Control of a Pan-Tilt Mechanism (PTM) angle for the bomb disposal robot Morolipi-V2 using inertial sensor measurement unit, x-IMU, has been done. The PTM has to be able to be actively controlled both manually and automatically in order to correct the orientation of the moving Morolipi-V2 platform. The x-IMU detects the platform orientation and sends the result in order to automatically control the PTM. The orientation is calculated using the quaternion combined with Madwick and Mahony f ilter methods. The orientation data that consists of angles of roll ( α ), pitch ( β ), and yaw ( γ ) from the x-IMU are then being sent to the camera for controlling the PTM motion (pan tilt angles) after calculating the reverse angle using position matrix method. Experiment results using Madwick and Mahony methods show that the x-IMU can be used to find the robot platform orientation. Acceleration data from accelerometer and flux from magneto meter produce noise with standard deviation of 0.015 g and 0.006 G, respectively. Maximum ab solute errors caused by Madgwick and Mahony method with respect to X- axis are 48.45º and 33.91º, respectively. The x-IMU im plementation as inertia sensor to control the Pan-Tilt Mechanism shows a good result, which the probability of pan angle tends to be the same with yaw and tilt angle equal to the pitch angle, except a very small angle shift due to the influence of roll angle.